Probabilidade de morrer no primeiro ano de vida em área urbana da região sul, Brasil Probability of dying in the first year of life in an urban area of Brazil - Regina K. Tanno de Souza; Sabina L.D. Gotlieb (Universidade de São Paulo, 1993)
Coorte constituída por 4.876 crianças nascidas vivas, em hospitais do Município de Maringá-PR (Brasil), em 1989, foi acompanhada com a finalidade de estimar a probabilidade de morrer no primeiro ano de vida. As variáveis de estudo foram sexo, peso ao nascer, idade da mãe, subgrupos etários e causa básica de morte. A probabilidade de morte no primeiro ano de vida foi estimada em 19,9 por mil, sendo que 77,3% dos óbitos ocorreram no período neonatal. As causas perinatais, juntamente com as anomalias congênitas, responderam por mais de 80% dos óbitos, e as doenças infecciosas e parasitárias, por apenas 1,1%. A probabilidade de morrer no primeiro ano de vida devido às afecções originadas no período perinatal foi superior nas crianças nascidas de parto normal (20,3 por mil) em relação à das nascidas por cesárea (9 por mil). O risco de morrer foi maior nos filhos de mulheres adolescentes, nas crianças nascidas com peso inferior a 2.500g. Os resultados chamam a atenção para a necessidade de melhorar a qualidade da assistência pré-natal, ao parto e ao recém-nascido e sugerem possível associação entre maior mortalidade e pior nível socioeconômico. A birth-cohort of 4,876 children born alive in hospital were selected and followed through up to the age of one year with a view to estimating the risk of dying in the first year of life. All of them were born in 1989, in one of the the seven hospitals of an urban area of Southern Brazil and the only requirement for belonging to the cohort was that of residence on the area. The selected variables were: sex, birthweight, age at moment of death, urderlying cause of death, and maternal age. The estimated probability of dying in the first year was of 19.9 per 1,000 (77.3% of the deaths occurred during the neonatal period). Perinatal causes and congenital malformations contributed to 80% of the deaths, and infectious diseases were the underlying cause of death in only 1.1% of the losses. The risk of dying in the first year of life due to afections arising during the perinatal period was higher among vaginally delivered babies (20.3 per 1,000) than it was for those born by caesarian section (9 per 1,000). A higher probability of death was present among infants born to adolescent mothers, and those with low birthweight (less than 2,500g). The results brought out the need for improving the quality of prenatal and infant care. They also suggested the hypothesis of a possible association between higher infant mortality and lower socio-economic level.